COVID-19 Dentistry-Related Aspects: A Literature Overview - Vittorio Checchi; Pierantonio Bellini; Davide Bencivenni; Ugo Consolo (Elsevier, 2021)
A new coronavirus (Sars-CoV-2) was detected in China at the end of 2019 and has since caused a worldwide pandemic. This virus is responsible for an acute respiratory syndrome (COVID-19), distinguished by a potentially lethal interstitial bilateral pneumonia. Because Sars-CoV-2 is highly infective through airborne contamination, the high infection risk in the dental environment is a serious problem for both professional practitioners and patients. This literature overview provides a description of the clinical aspects of COVID-19 and its transmission, while supplying valuable information regarding protection and prevention measures.